Parents Perceptions Of Semarang Tri Tunggal Elementary School Students Against Childhood Obesity - Christiana, Metta; Nurcahyo, Andi (Economics and Business Solutions Journal, 2018)
The purpose of this study is to find out how the perceptions of parents of SD Tri Tunggal students that fat children are funny and healthy can be formed. Type of this research is qualitative with phenomenology approach. Data were collected by in-depth interview and observation. Research subjects as many as 8 people consisting of 5 parents of Primary School Tri Tunggal, 1 child pediatrician, 1 nutritionist, 1 sports expert. Data were analyzed by content analysis. The results showed that the perception of parents who consider the fat child is funny and healthy is formed because through the first process they like to see and feel the pleasant sensation to see and hug the fat child, plus they have a feeling of proud to have fat children because they consider successfully taking care of their children. After going through the first process, parents lack the hope, motivation and a firm attitude to reduce child obesity. Parents assume if the fat little boy is still funny and healthy. The next process parents have had some bad experience about childhood obesity but looks not considered a serious experience to be addressed, resulting in a learning process that is very less for parents. In the end, parents have the wrong perception of childhood obesity.